Unravelling rate-determining step and consequence of O2-or H2O-assisted, wet CO transformation on catalytic CuO-CeO2 domains via interfacial engineering - Kim, Dong Ho; Oh, Sang-Ho; Ha, Heon Phil; Joo, Young-Chang; Kim, Jongsik (Elsevier BV, 2023)
CO generates CO2, a feedstock of chemicals including alcohols, alkenes, etc., through exothermic oxidation/ water-gas shift (WGS) on CuO-CeO2 interfaces. However, CO oxidation/WGS with wet, low-temperature gases have been partially explored with regard to surface dynamics, rate laws, rate-determining steps, and catalytic consequences. This study clarifies the aforementioned conundrums via control runs and kinetic assessments. Two CuO-CeO2 interfaces were engineered to possess comparable quantities of CO/H2O-accessible Cu+/2+ species or O2/H2O-accessible mobile (OM), labile (OL), and vacant oxygens, yet, provide distinct binding strengths with CO (ECO), OM (EOM), and H2O (EH2O) alongside with dissimilar H2O-accessible surface areas (SH2O). 18O2-labelling control runs and energy barriers (EBARRIER) of the CuO-CeO2 interfaces corroborated that OM migration outweighed OL migration as the rate-determining step for CO oxidation. The EBARRIER/SH2O values of the CuO-CeO2 interfaces demonstrated that H2O scission overrode CO2 evolution as the rate-determining step for the WGS. CO oxidation competed with yet outperformed WGS in converting CO using wet, low-temperature gases, highlighting the importance of lowering the ECO/EOM values in boost OM migration on CuO-CeO2 interfaces and reducing their EH2O values for hindering WGS. These findings can promote the low-temperature CO transformation performance maximum-obtainable on CuO-CeO2 interfaces.